2013
DOI: 10.2217/pme.13.85
|View full text |Cite
|
Sign up to set email alerts
|

Community Pharmacists‘ Attitudes Towards Clinical Utility and Ethical Implications of Pharmacogenetic Testing

Abstract: Aim To examine community pharmacists’ attitudes towards pharmacogenetic (PGx) testing, including their views of the clinical utility of PGx and the ethical, social, legal and practical implications of PGx testing. Methods A web-based survey administered to 5600 licensed community pharmacists in the states of Ohio and Pennsylvania (USA). Results Of 580 respondents, 78% had a Bachelor of Science degree in pharmacy and 58% worked in a chain drug store. Doctors of pharmacy-trained pharmacists had a significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
91
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(99 citation statements)
references
References 20 publications
8
91
0
Order By: Relevance
“…25 Three surveys were qualitative, that used one or combination of semi structure questionnaire, one-day meeting and case scenarios, 9,22,26 and with regard to design, four research were cohort study, 19,21,24,26 while the rest nine were Crosssectional studies, 9,12,15,16,18,[22][23][24][25] Pharmacogenetics or PG or pharmacogenetic testing and pharmacists or pharmacy students were discussed in all the articles. Table 1 presented the summary of included researches in this systematic review.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Three surveys were qualitative, that used one or combination of semi structure questionnaire, one-day meeting and case scenarios, 9,22,26 and with regard to design, four research were cohort study, 19,21,24,26 while the rest nine were Crosssectional studies, 9,12,15,16,18,[22][23][24][25] Pharmacogenetics or PG or pharmacogenetic testing and pharmacists or pharmacy students were discussed in all the articles. Table 1 presented the summary of included researches in this systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies have had a response rate of less than 60% for pharmacists, 12,15,16,18,19,23 while the remaining six have response rate more than 60%, 9,17,21,22,25 Only three researches used statistical analysis in questionnaire validation; 12,18,21 two studies used pilot study to validate the questionnaire in the studies; 17,19 majority of studies used experts reviews or kept silence on validity of questionnaire. 9,15,16,[22][23][24][25][26] In total 4,624 pharmacists participated in the reviewed articles.…”
Section: Resultsmentioning
confidence: 99%
“…24 But this is an ongoing effort because there are still pharmacists who have expressed their lack of confidence in this matter. 8,23,25,26 Pharmacogenomic education in PharmD programs has grown rapidly. In 2005, only 32 out of 41 (78%) pharmacy schools that answered a survey described that they have some components of pharmacogenomics in their curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…Another previous study in USA in 580 community pharmacists showed that around 87% community pharmacists had positive attitude toward pharmacogenetic test and around 57% realized their role in giving counseling to the patients about pharmacogenetic [11]. Moreover, in Qatar, the study about awareness and attitude towards pharmacogenetic was conducted among the pharmacists and doctors.…”
Section: Introductionmentioning
confidence: 99%
“…We used the questionnaire about knowledge, awareness and attitude of pharmacists towards pharmacogenetic from the previous study [11,13]. We translated the questionnaire into Bahasa Indonesia version at the Center of Language Practices Universitas Ahmad Dahlan.…”
Section: Introductionmentioning
confidence: 99%